Analisis Sastra Lisan Mak Tiolo Suku Bambam: Perspektif Sastra Lisan Ruth Finnegan - Kussuji Indrastuti, Novi Siti; Elga , Renni (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2024)
This study aims to determine the composition, style, and performance in Ma' Tiolo oral literature in the Bambam tribe. This study uses a qualitative method with Ruth Finnegan's oral literature theory. The object of this study is Ma' Tiolo oral literature in the Bambam tribe with data collection techniques, namely recording, (audio and visual), taking notes, interviews, observations, and literature studies. The research location in this study is located in Tabulahan sub-district, Mamasa district, West Sulawesi province. The results of this study are that the composition of Ma' Tiolo oral literature does not use memorized sentences and is in accordance with the creativity of the storyteller, the storyteller has sentences (with uncertain word choices) to open and close the storytelling process, and the story told always has a moral message at the end of the story. For style and performance, it was found that in general the theme or setting in the story is family or friendship, the storyteller is more silent when telling the story, there is interaction in the storytelling process, and Ma' Tilo can be done by anyone if they can speak Bambam and know ancient stories such as some of the stories presented in this study.